The gold in these hills [large type] - Bischof, Joanne (Center Point Large Print, 2021)
"Upon arriving in Kenworthy, California, mail-order bride Juniper Cohen is met by the pounding of the gold mine, an untamable landscape, and her greatest surprise of all: the kind and loving man who awaits her. But when the mine proves empty of profit, and when Juniper's husband, John, vanishes, Juniper is left to fend for herself and her young daughter in the dwindling boomtown that is now her home. Juniper pens letters to her husband but fears she is waiting on a ghost. Perhaps worse, rumors abound claiming the man she loves could be an outlaw. Surviving in a ghost town requires trusting the kindness of a few remaining souls, including the one who can unlock the mystery of her husband's disappearance - and Juniper's survival depends not only upon these friends but also the strength of heart she must fight to maintain. Present day. Trying to escape the heartache of his failed marriage, Johnny Sutherland throws himself into raising his children and restoring a hundred-year-old abandoned farmhouse in what was once known as Kenworthy, California, in the San Jacinto Mountains. While exploring its secrets he uncovers Juniper's letters and is moved by the handwritten accounts that bear his name- and as a love story from the past touches his own world, Johnny might discover yet that hope and resilience go hand in hand"--